Emerging carbon-based flexible anodes for potassium-ion batteries: Progress and opportunities - Li, Wenbin; Yang, Zihao; Zuo, Jiaxuan; Wang, Jingjing; Li, Xifei (Frontiers in Chemistry, 2022)
In recent years, carbon-based flexible anodes for potassium-ion battery (PIB) are increasingly investigated owing to the low reduction potential and abundant reserve of K, as well as the simple preparation process of flexible electrode. In this review, three main problems on the pristine carbon-based flexible anodes are summarized: excessive volume change, repeated SEI growth and low affinity with K+, which thus leads to severe capacity fade, sluggish K+ diffusion dynamics and limited active sites. In this regard, recent progress on the various modification strategies are detailedly introduced, which are categorized as hetero atom-doping, coupling with metal and chalcogenides nano particles, as well as coupling with other carbonaceous materials. It is found that the doping of heteroatom can bring the five enhancement effects of increasing active sites, improving electrical conductivity, expediting K+ diffusion, strengthening structural stability and enlarging interlayer spacing. The coupling of metal and chalcogenides nano particles can largely offset the weakness of the scarcity of K+ storage sites and the poor wettability of pristine carbon-based flexible electrode. The alloy nanoparticles consisted of the electrochemically active and inactive metal can concurrently gain the stable structure and high capacity in comparison to mono-metal nano particles. The coupling of the carbonaceous materials with different characteristics can coordinate the advantages of the nano structure from graphite carbon, the defects and vacancies from amorphous carbon as well as the independent structure from support carbon. Finally, the emerging challenges and opportunities on the development of carbon-based flexible anodes are presented